Idiopathic Granulomatous Mastitis: In Search of a Therapeutic Template - Khan, Sadia Armin; Ali, Abu Ahmed Ashraf (Journal of Surgical Sciences, 2019)
Background: Granulomatous mastitis also known as granulomatous inflammatory lesionsof the breast can be divided into idiopathic granulomatous mastitis and granulomatousmastitis occurring as a rare secondary complication of a great variety of other conditions.Treatment is radically different for idiopathic granulomatous mastitis and other granulomatouslesions of the breast, the precise diagnosis is therefore very important. Objectives: The purpose of this study was to find the clinicopathological features ofidiopathic granulomatous mastitis, as well as the authors' experience with surgicaltreatment of these patients. Methods and Materials: A hospital based retrospective study done with twenty diagnosedpatients of idiopathic granulomatous mastitis enrolled from department of surgery, Ad-dinwomen's.medical college hospital, Dhaka in the period between July 2012- July 2015. Results: Mean age of presentation was 38.1 years. All patients had a history of childbirthand breastfeeding. Sixteen (80%) patients were premenopausal. The main clinical featurewas a mass in the breast in all patients and clinical findings suggesting an infection accompaniedthe mass in seven patients (35%). Surgery was the definitive procedure in allpatients. Wide local excision done in all patients. None of the patients received steroids.Median follow-up time was 12 months. During follow-up, two patients (10%) presented withrecurrence. All patients with recurrence had a mass in their breasts on the same side ofprevious disease. Conclusion: Increased recognition of this disease will improve its understanding andmanagement. Long-term follow-up is necessary. Journal of Surgical Sciences (2016) Vol. 20 (2) :51-54